2019
DOI: 10.1080/01442872.2019.1618816
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting deliberative policy analysis through systemic co-inquiry: some experiences from the implementation of the Water Framework Directive in England

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…We would also assert that for social-ecological systems research to have practical influence, it needs to go beyond interdisciplinarity to become transdisciplinary, i.e., to develop and pursue a shared research objective with actors in society (such as land managers and other stakeholders), by "unsettling the distinction between research providers and research users" (Mitchell et al 2017, p. 2). For transdisciplinary research to become an effective process of learning through active adaptive management requires intervening in the systems being studied (Midgley 2003) through co-inquiry with those who are part of these systems (Foster et al 2019;Allan et al 2020). Reflection on practice is also essential (Stringer et al 2006) to enhance learning and identify what could be improved.…”
Section: Contributing To Improved Water Management Using the Practicementioning
confidence: 99%
See 1 more Smart Citation
“…We would also assert that for social-ecological systems research to have practical influence, it needs to go beyond interdisciplinarity to become transdisciplinary, i.e., to develop and pursue a shared research objective with actors in society (such as land managers and other stakeholders), by "unsettling the distinction between research providers and research users" (Mitchell et al 2017, p. 2). For transdisciplinary research to become an effective process of learning through active adaptive management requires intervening in the systems being studied (Midgley 2003) through co-inquiry with those who are part of these systems (Foster et al 2019;Allan et al 2020). Reflection on practice is also essential (Stringer et al 2006) to enhance learning and identify what could be improved.…”
Section: Contributing To Improved Water Management Using the Practicementioning
confidence: 99%
“…Co-inquiry is a deliberative research process to institutionalise collaborative action by research providers and users as a community in response to the complex situations they are navigating. It relies on iterative social learning as the means to improve outcomes (Foster et al 2019). In our case, the actions undertaken as a collaboration among researchers, research users and research beneficiaries used the methodology of intervention: purposefully co-creating change in the system being studied (Midgley 2003).…”
Section: What We Have Been Doingmentioning
confidence: 99%
“…In order to achieve positive outcomes, interactions between policymakers and interest groups should be based on cooperation and trust. The WFD acknowledges this and advocates the principle of public participation in order to allow all interests to be considered during policymaking [73,74]. We consider actors' interests, in particular the extent to which they are represented in the process, and how policymakers successfully achieve a synthesis between contrasting priorities without compromising the adoption of effective policies [75].…”
Section: Cooperationmentioning
confidence: 99%
“…These studies generally linked increased public participation stemming from the WFD implementation process to increased quality and increased acceptability of policy outputs [39][40][41], while other contributions highlighted that important role of third sector River Trusts charities in creating partnerships with the EA [95,96]. In general, studies conducted in England concluded that in spite of attempts to try different and more bottom-up approaches, participatory experiences have been highly variable [97] and, further, this potential had not been fully exploited [43,74,98,99]. In addition, since 2013, the UK Government has attempted a Catchment Based Approach (CaBA) to foster active stakeholder engagement and to strengthen existing and newly formed catchment partnerships [100].…”
Section: Implementation Of the Wfd In The Case Settingsmentioning
confidence: 99%
“…The paper begins with a brief review of the literature on community resilience and hazards, focusing in on resilience and wildfire management. The research setting and methods are introduced and our development of a systemic co-inquiry (Foster et al 2019) conducted with research participants is described. Findings are presented in terms of the scale of organization and leadership characteristics of our key participants, vulnerabilities they identify, and insights gained from their experiences and practice.…”
Section: Introductionmentioning
confidence: 99%